Making sense of critical pedagogy in l2 education through a collaborative study group (2014)
In this article we discuss our experiences in the process of understanding critical pedagogy within an English teachers’ study group which was created for the purpose of learning how to teach language from a critical perspective. We particularly focus on the challenges of meaning making around critical pedagogy, as we realized that we were not all able to similarly enter this discourse. To illustrate our processes of understanding theory individually and collectively, some of the group members’ narratives are used as examples of our different perspectives. We argue that making sense of critical pedagogy, as part of a process of professional development, implies spaces and situations of personal confrontation with theory and support in collaborative learning through dialogue.Presentamos nuestras experiencias del proceso de comprender la pedagogía crítica por parte de un grupo de profesores de inglés, que fue creado con el propósito de aprender cómo se puede enseñar la lengua desde una perspectiva crítica, en diferentes contextos en Medellín. Nos enfocamos particularmente en los desafíos que implica construir significado sobre la pedagogía crítica cuando no todas las integrantes podían acceder a este discurso de la misma manera. Para ilustrar nuestro proceso de comprensión individual y grupal de la teoría, utilizamos las narrativas de algunas integrantes del grupo como ejemplos de nuestras diversas perspectivas. Planteamos que darle sentido a la pedagogía crítica como parte de un proceso de desarrollo profesional implica espacios y situaciones de confrontación personal con la teoría, así como apoyo en el aprendizaje colaborativo a través del diálogo.